Investigation and Study on the Current Status of First Aid Competence among Preschool Education Majors - Lan, Lan (Transactions on Social Science, Education and Humanities Research, 2024)
Understanding the current status of emergency response capabilities among preschool education majors at our institution is crucial for providing theoretical foundations and recommendations for the development and instructional design of subsequent practical courses in emergency nursing skills. A cluster sampling method was employed to survey the knowledge, attitudes, and behaviors related to emergency aid among the preschool education majors currently enrolled at our institution. The questionnaire was designed with reference to related literature and was modified accordingly. It analyzed the current state of emergency response capabilities among these students and their needs for emergency knowledge and skills. The accuracy rate of emergency knowledge among preschool education majors is generally low, yet there is a willingness to learn about emergency aid and skills. It is recommended to strengthen systematic theoretical education and to establish practical courses related to emergency nursing skills to enhance the emergency knowledge and skills of preschool education majors.